Chiral pool approach for the synthesis of functionalized amino acids: synthesis of antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (R)-lacosamide 1 has been achieved from N-Boc-N,O-isopropylidene-l-serinol 2 which could easily be obtained from natural l-serine. Our synthesis of 1 starting from 2 using chiral pool strategy resulted in 54% overall yield.

Norepinephrine alkaloids as antiplasmodial agents: Synthesis of syncarpamide and insight into the structure-activity relationships of its analogues as antiplasmodial agents - Aratikatla, Eswar K.; Valkute, Tushar R.; Puri, Sunil K.; Srivastava, Kumkum; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2017)
Syncarpamide 1, a norepinephrine alkaloid isolated from the leaves of Zanthoxylum syncarpum (Rutaceae) exhibited promising antiplasmodial activities against Plasmodium falciparum with reported IC50 values of 2.04 mu M (D6 clone), 3.06 mu M (W2 clone) and observed by us 3.90 mu M (3D7 clone) and 2.56 mu M (K1 clone). In continuation of our work on naturally occurring antimalarial compounds, synthesis of syncarpamide 1 and its enantiomer, (R)-2 using Sharpless asymmetric dihydroxylation as a key step has been accomplished. In order to study structure-activity-relationship (SAR) in detail, a library of 55 compounds (3-57), which are analogues/homologues of syncarpamide 1 were synthesized by varying the substituents on the aromatic ring, by changing the stereocentre at the C-7 and/or by varying the acid groups in the ester and/or amide side chain based on the natural product lead molecule and further assayed in vitro against 3D7 and K1 strains of P. falciparum to evaluate their antiplasmodial activities. In order to study the effect of position of functional groups on antiplasmodial activity profile, a regioisomer (S)-58 of syncarpamide 1 was synthesized however, it turned out to be inactive against both the strains. Two compounds, (S)-41 and its enantiomer, (R)-42 having 3,4,5-trimethoxy cinnamoyl groups as side chains showed better antiplasmodial activity with IC50 values of 3.16, 2.28 mu M (3D7) and 1.78, 2.07 mu M (I(1), respectively than the natural product, syncarpamide 1. Three compounds (S)-13, (S)-17, (S)-21 exhibited antiplasmodial activities with IC50 values of 6.39, 6.82, 6.41 mu M against 3D7 strain, 4.27, 7.26, 2.71 mu M against K1 strain and with CC50 values of 147.72, 153.0, >200 mu M respectively. The in vitro antiplasmodial activity data of synthesized library suggests that the electron density and possibility of resonance in both the ester and amide side chains increases the antiplasmodial activity as compared to the parent natural product 1: The natural product syncarpamide 1 and four analogues/homologues out of the synthesized library of 55, (S)-41, (R)-42, (S)-55 and (S)-57 were assayed in vivo assay against chioroquine-resistant P. yoelii (N-67) strain of Plasmodium. However, none of the five molecules, 1, (S)-41, (R)-42, (S)-55 and (S)-57 exhibited any promising in vivo antimalarial activity against P. yoelii (N-67) strain. Compounds 4, 6, 7 and 11 showed high cytotoxicities with CC50 values of 5.87, 5.08, 6.44 and 14.04 mu M, respectively. Compound 6 was found to be the most cytotoxic as compared to the standard drug, podophyllotoxin whereas compounds 4 and 7 showed comparable cytotoxicities to podophyllotoxin. (C) 2017 Elsevier Masson SAS. All rights reserved.

Enantioselective synthesis of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones and their application to the synthesis of novel highly potent antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (ACS Omega, 2020)
Racemic and enantioselective syntheses of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones have been achieved using Horner-Wadsworth-Emmons olefination of trityl protected alpha-phenyl-alpha-amino aldehydes with tetraethyl methylenediphosphonate and diethyl ((phenylsulfonyl)methyl)phosphonate, respectively, without any racemization. The present strategy has also been successfully applied to the synthesis of peptidyl vinyl phosphonate and peptidyl vinyl sulfone derivatives as potential cysteine protease inhibitors of Chagas disease, K11002, with 100% de. The developed synthetic protocol was further utilized to synthesize hybrid molecules consisting of artemisinin as an inhibitor of major cysteine protease falcipain-2 present in the food vacuole of the malarial parasite. The synthesized artemisinin-dipeptidyl vinyl sulfone hybrid compounds showed effective in vitro inhibition of falcipain-2 and potent parasiticidal efficacies against Plasmodium falciparum in nanomolar ranges. Overall, the developed synthetic protocol could be effectively utilized to design cysteine protease inhibitors not only as novel antimalarial compounds but also to be involved in other life-threatening diseases.

Short review of synthetic routes for the antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Organic Process Research & Development, 2020)
The disease epilepsy affects people of all ages and is due to a chronic neurological disorder in the brain. According to a report by the World Health Organization, epilepsy is one of the most common global neurological diseases. (R)-Lacosamide (Vimpat) was introduced by UCB Pharma in 2008 for the treatment of partial-onset seizures in patients suffering from epilepsy. This review summarizes all of the available synthetic strategies reported for (R)-lacosamide, which will help medicinal chemists in the further development of its synthesis.
Keywords: antiepileptic drug; epilepsy; lacosamide; serine derivative; synthesis

Combating multi-drug resistant malaria parasite by inhibiting falcipain-2 and heme-polymerization: Artemisinin-peptidyl vinyl phosphonate hybrid molecules as new antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Rana, Kalpeshkumar C.; Datta, Gaurav; Asad, Mohd; Sundararaman, Srividhya; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Artemisinin-based combination therapies (ACTs) have been able to reduce the clinical and pathological malaria cases in endemic areas around the globe. However, recent reports have shown a progressive decline in malaria parasite clearance in South-east Asia after ACT treatment, thus envisaging a need for new artemisinin (ART) derivatives and combinations. To address the emergence of drug resistance to current antimalarials, here we report the synthesis of artemisinin-peptidyl vinyl phosphonate hybrid molecules that show superior efficacy than artemisinin alone against chloroquine-resistant as well as multidrug-resistant Plasmodium falciparum strains with EC<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">50<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in pico-molar ranges. Further, the compounds effectively inhibited the survival of ring-stage parasite for laboratory-adapted artemisinin-resistant parasite lines as compared to artemisinin. These hybrid molecules showed complete parasite clearance in vivo using P. berghei mouse malaria model in comparison to artemisinin alone. Studies on the mode of action of hybrid molecules suggested that these artemisinin-peptidyl vinyl phosphonate hybrid molecules possessed dual activities: inhibited falcipain-2 (FP-2) activity, a P. falciparum cysteine protease involved in hemoglobin degradation, and also blocked the hemozoin formation in the food-vacuole, a step earlier shown to be blocked by artemisinin. Since these hybrid molecules blocked multiple steps of a pathway and showed synergistic efficacies, we believe that these lead compounds can be developed as effective antimalarials to prevent the spread of resistance to current antimalarials.